A new mdr-1 encoded P-170 specific monoclonal antibody: (6/1C) on paraffin wax embedded tissue without pretreatment of sections. Issue 6 (June 1997) - Moran, E; Larkin, A; Doherty, G; Kelehan, P; Kennedy, S; Clynes, M
Abstract : AIMS: The generation and characterisation of a monoclonal antibody that specifically recognises the mdr-1 encoded protein, P-glycoprotein (P-170), on routinely processed formalin fixed, paraffin wax embedded tissue sections. METHODS: The monoclonal antibody, designated 6/1C, was produced following a combination of in vivo and in vitro immunisation regimens in Balb/c mice with a synthetic 12 amino acid peptide that corresponds to amino acids 21-32 (believed to be intracellularly located) of P-170 and has insignificant homology with the mdr-3 encoded P-170. Antibody 6/1C was characterised by western blotting and immunocytochemistry on cytospins of paired multidrug resistant or sensitive cell lines, including mdr-1 and mdr-3 transfected cells, and by immunohistochemistry on normal and malignant formalin fixed paraffin wax embedded tissue sections. RESULTS: Antibody 6/1C showed a single band at 170 kDa on western blots of multidrug resistant cell lysates and mdr-1 transfected cell lysates that was absent on similar preparations of drug sensitive cells and mdr-3 transfected cells. Immunocytochemical studies on cytospins of multidrug resistant cells and mdr-1 transfected cells revealed strong inner plasma membrane/cytoplasmic staining. Staining was negligible on drug sensitive cells and cells transfected with the mdr-3 gene. Immunohistochemical studies on formalin fixed, paraffin wax embedded normal adult kidney, liver, and breast tissue and a range of fetal tissues exhibited staining patterns of a variety of secretory surfaces consistent with documented mdr-1 specific staining. Specific staining of malignant cells in similarly treated sections of breast tumours was seen also with antibody 6/1C. Staining on paraffin wax embedded tissue with this antibody did not require any pretreatment of tissue sections. CONCLUSIONS: This new monoclonal antibody, chosen for its specificity with the mdr-1 encoded P-170 and its reactivity on routinely fixed paraffin wax embedded tissue samples without pretreatment, appears to be useful for the investigation of P-170 in archival material. It is especially useful for retrospective studies on pretreatment and post-treatment tissue sections, and could help establish when and how rapidly mdr-1 associated drug resistance develops during chemotherapeutic regimens. Immunohistochemical assessment of P-170 expression in many cancers has potential for diagnostic purposes and may influence the choice of chemotherapeutic drugs used in the treatment of refractory tumours.